Pengaruh Insentif dan Kepuasan Kerja Terhadap Kinerja Pegawai Melalui Semangat Kerja Sebagai Variabel Intervening pada PT. Keaj Beaute Group - Ferry Hidayat; Victor (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the effect of incentives and job satisfaction on employee performance, with work enthusiasm as an intervening variable at PT. Keaj Beaute Group. The research employs a quantitative approach using descriptive methods. Data were collected through questionnaires distributed to 30 employees and analyzed using multiple linear regression and path analysis. The results show that incentives do not have a significant effect on either work enthusiasm or employee performance. Job satisfaction significantly influences work enthusiasm but has no direct impact on performance. Work enthusiasm has a significant positive effect on employee performance and serves as a mediating variable between job satisfaction and employee performance, but does not mediate the relationship between incentives and performance. These findings highlight the importance of enhancing work enthusiasm through effective management of job satisfaction to achieve optimal employee performance.